Effectiveness of Temporins for the Treatment of HPV Infections - Eshaana Janardhan Raichur (International Journal of Cell Biology and Cellular Functions, 2024)
Objectives: Human papillomavirus (HPV), especially high-risk variants like type-16 have been linked to the formation of malignant tumors. HPV-16 has been implicated in most cases of cervical cancer in women. This study aims to assess the effectiveness of three types of temporin molecules, i.e., antiviral peptides secreted by certain frog species, for the inhibition of the viral L1 protein. Methods: In the present study, various computational tools were used to find the temporin molecule that was most effective in inhibiting the attachment of the L1 viral major capsid protein of HPV type-16 to the heparan sulfate proteoglycan residues present on the basement membrane of the host cell. HPEPDOCK 2.0 and pyDockWEB servers were used to carry out protein-peptide and protein–protein docking, respectively. Binding affinity scores revealed the efficiencies of the different temporin molecules in inhibiting the action of the L1 protein. Results: According to the results obtained from this docking study, the temporin-L peptide, which was isolated from Rana temporaria was found to be the most efficient in preventing the attachment of the viral L1 major capsid protein to the host cell HSPG residues present on the basement membrane, thereby hindering the mechanism of viral entry. Conclusion: Further studies can be conducted on the mechanism of action of the temporin-L antiviral peptide. It can be a potential new therapeutic option for the treatment and management of high-risk HPV infections. Further research can be conducted on the temporin-L molecule for the formulation of new antiviral therapeutics for the treatment of HPV-16 infections. Temporins can be formulated into topical creams or gels, which could be applied directly to genital warts caused by HPV. These formulations might help reduce the size and discomfort of warts or even promote their clearance.
Keywords: Human papillomavirus; L1 protein; antiviral peptides; temporins